Design of Robotic Arm Control System Mimics Human Arm Motion - Al-Ammri, A. Salam; Taki, Ghaith A. (Al-Khwarizmi Engineering Journal, 2017)
This paper presents a control system to make the robotic hand mimic human hand motion in real time and offline mode. The human hand tracking system is a wearable sensing arm (potentiometers) used to determine the position in space and to sense the grasping task of human hand. The maskable sensing arm was designed with same geometrical arrangement of robotic hand that needs to be controlled. The control software of a robot was implemented using Visual Basic and supported with graphical user interface (GUI). The control algorithm depends on joint to joint mapping method to match between the motions at each joint of portable sensing arm with corresponding joint of a robot in order to make the robot mimic the motion.